Sustitución parcial de pulpa de zapallo (Curcubita máxima Dutch) en la elaboración de mermelada de piña (Annanas Cosmosus L). - Maldonado Sarango, Karol Liseth (2023)
The pumpkin (Curcubita maxima Dutch) is a vegetable from which we are not taking the necessary advantage of its nutritional potential we should, therefore causing waste since there are no alternative products with a similar added value, owing to this, the objective that has been raised for this investigation is to contribute generate an agroproductive alternative for the farmers of the Chuquiribamba parish by making pineapple jam using pumpkin pulp; for which, 6 processes were proposed including different portions of pumpkin and pineapple. The establishment of the best process was made based on the results from the organoleptic analysis, then it was conducted the physical-chemical analysis of the defined process, later, the production costs and retail price (profit margin of 32 %) were determined, and finally, the results of the investigation were socialized to the producers of the Chuquiribamba parish. The T4 process has been greatly accepted by the community, since it showed the highest qualifications in the attributes of colour, aroma, consistency and flavour; after the quality evaluation to the jam through physicochemical analysis, the following results were acquired: humidity 6,81%, carbohydrates 88,45 %, protein 2,50 %, fiber 1,00 %, ashes 1,24 %, pH 3,40 %, acidity 0.47 % and ºBrix 52.10%; evidencing that it complies with the characteristics according to national regulations (INEN 419 and 2825); finally, it was determined that the costs of production and sale price to the public for a container of 280 grams of net weight of jam are 1.14 and 1.50 US dollars, respectively; through this investigation, we are contributing to the use of the pumpkin cultivation in the Chuquiribamba parish, using the perk of added value and reduction of waste, hence allowing producers to obtain a better income. Keywords: pumpkin, pineapple, jam, physical-chemical analysis and Chuquiribamba.